Factors Influencing of Tax Evasion: Tax Sanctions, Tax Understanding, and Love of Money. - Yosi Ika Putri; Tutty Nuryati; Tri Yulaeli; Beti Nurbaiti; Endah Prawesti Ningrum (Research Trend in Technology and Management, 2025)
This research discusses how tax sanctions, tax understanding, and love of money influence taxpayers' perceptions of tax evasion. The results from the literature review indicate that the influence of these three factors is not always consistent. Tax sanctions can make people afraid to evade taxes if the law is enforced fairly, but they can also lead people to justify evasion if they feel the law is unjust. Tax understanding sometimes encourages compliance, but it can also be exploited to find legal loopholes. Meanwhile, love of money can tempt people to evade taxes for profit, but it can also make them compliant for fear of losing money due to sanctions. Therefore, the influence of these three factors heavily depends on the situation and the values held by each individual